The influence of workload, training and team work on the performance of public works department employees, spatial and land planning in the Riau Islands Province with organizational commitment as an intervening variable - Hendriyan Saputra; Ngaliman Ngaliman; Bambang Satriawan (Review of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This research analyzes the influence of workload, training and teamwork on the performance of employees of the Public Works, Spatial Planning and Land Management Department of Riau Islands Province with organizational commitment as an intervening variable. Research Methodology: In 2020, there were 6 packages or 6.59% of the 91 work packages at the Riau Islands Province PUPP Service that experienced payment delays. Meanwhile, in 2021 there was an increase, namely 68 packages or 31.19% of the 218 packages experienced payment delays. Meanwhile, in 2022 there will be 10 packages or 3.14% of the 318 packages experiencing payment delays. Using primary data from 115 employees of the Public Works, Spatial Planning and Land Services of Riau Islands Province. Results: this research found that teamwork has no direct significant effect on performance. In contrast, workload and training were shown to have a significant influence on performance, highlighting the importance of work themes for improving employee performance. Organizational commitment is also proven to be a significant mediator between workload, training and teamwork on performance. Recommendation: The proposed recommendation is to focus on improving employee teamwork and other aspects that have a more direct influence on organizational commitment to improving the performance of employees of the Public Works, Spatial Planning and Land Management Department of Riau Islands Province